Anti cancer effect of paddy husk extracts in human salivary gland epidermoid cancer cells in vitro model - Al-Azazi, Entesar Ahmed Abdullah (2024)
Global agriculture produces millions of tons of waste yearly. Paddy husk is an inedible agriculture waste obtained during the process of rice milling. Studies reported that it has chemopreventive potential due to the presence of related phytochemicals. The aim of this study is to elucidate the presence of anti-cancer related phytochemicals from paddy husk extract and evaluate its inhibitory and anti-proliferative effects against human submaxillary salivary gland epidermoid carcinoma cells (HTB-41). Two types of solvent for paddy husk extract have been used; water and aqueous methanol. The phytochemical constituents of paddy husk extracts were identified using GC-MS. The inhibitory activity and cytotoxicity analysis was calculated using Trypan Blue Exclusion Assay (TBEA). Apoptosis and cell cycle analysis were evaluated by flow cytometer, and cell morphology post treatment was analysed ultrastructurally, while Western blot was performed for proteomic analysis. Our results showed presence of vitamin E and other phytochemicals in paddy husk extracts. Both water and aqueous methanol extracts demonstrated inhibitory activity on HTB- 41 cells where IC50 dose of water extract (400 μg/ml) managed to reduce cell viability to 53.0 % and IC50 dose of aqueous methanol extract (200 μg/ml) managed to reduce cell viability to 51.12 % without exhibiting any significant cytotoxic effects. Apoptosis analysis revealed that water and aqueous methanol extracts induce apoptosis effect on HTB-41 as supported with microscopic findings of cell shrinkage, membrane blebbing and apoptotic bodies, meanwhile, Hoechst 33342 staining showed nuclear shrinkage and fragmentation. Flow cytometry analysis demonstrated that paddy husk extracts promote a significant amount of apoptotic cellular population from 76.00% (untreated) to 47.86% (paddy husk water extract) and 43.13% (paddy husk aqueous methanol) and arresting the cells at S-phase from 19.90% (control) to 36.90 % (paddy husk aqueous methanol extract) and 27.86 % (paddy husk water extract). Western blot analysis reveals that apoptosis was induced through caspase 3-mediated intrinsic pathway. Pro-apoptotic and tumour suppressor proteins; Bax, p27kip1 expressed higher (P <0.05), while anti-apoptotic protein, Bcl-2 downregulated after treatment (P <0.01). This leads to increase of caspase 9 expression which in turn activate caspase 3 and 7 leading to cell apoptosis. In conclusion, the presence of phytochemicals in paddy husk especially in aqueous methanol extract successfully showed better inhibitory and anti-proliferative effects on the human submaxillary salivary gland epidermoid carcinoma cells (HTB-41), while it acted in a tumour-selective manner by not inducing any significant changes on human gingival fibroblast cell (HGF-1).